Drafting & design for architecture & construction - Hepler, Dana J.; Hepler, Donald E.; Wallach, Paul Ross (Delmar Cengage Learning, 2013)
Presents architectural drafting and design concepts in the order usually practiced by professional architects. This title covers Computer-Aided Design (CAD) in an introductory chapter along with a series of inserts throughout to provide examples of how CAD is used to perform specific architectural drafting functions.